Efficacy of a mobile-based self-directed parent management training for parents of children with attention-deficit/hyperactivity disorder with or without oppositional defiant disorder: a randomized controlled trial - Döpfner, Manfred; Görtz-Dorten, A.; Häge, Alexander; Handermann, F.; Sulprizio, L.; Hellmich, M.; Vogel, D.; Ruhmann, M.; Althen, H.; Karus, M.; Banaschewski, Tobias (European child & adolescent psychiatry, 2025)
Preliminary empirical evidence supports the efficacy of digital parent management training (d-PMT) in the treatment of externalizing behavior problems in children. This study investigated the efficacy of a mobile-based self-directed d-PMT for parents of children aged 4-11 years with attention-deficit/hyperactivity disorder (ADHD) with or without oppositional defiant disorder (ODD), and without pharmacological and/or behavioral therapy. Participants were randomized 1:1 to d-PMT (hiToco®) plus treatment as usual (TAU) or TAU only for 16 weeks. The primary outcome was a reduction of parent-rated externalizing problem behavior including symptoms of ADHD and ODD. Secondary outcomes included parent-rated ADHD symptoms only, ODD symptoms only, and functional impairment of the child as well as parenting behavior and family strain. Sixty-five participants were randomized to the dPMT + TAU group (n = 34) or the TAU group (n = 31). All children had a clinical diagnosis of ADHD; clinically diagnosed ODD was reported in 9 children (26.5%) in the d-PMT + TAU group and 13 children (42%) in the TAU group. The mean ± SD age of the children was 8.4 ± 1.7 years (69.2% boys). On average, participants used the program for 8 h in total. Regarding the primary outcome, significant treatment effects favoring the d-PMT + TAU group compared to the TAU group were observed at week 12 (W12) and W16 (Cohen’s d at W12: 0.74; at W16: 0.48). Post-hoc analyses showed that 50% of the children in the d-PMT + TAU group compared to 30% in the TAU group were reliably recovered or improved. Significant treatment effects in favor of the d-PMT + TAU group were also observed for all secondary variables. Our findings suggest that a mobile-based self-directed d-PMT for parents may play an important role in the multimodal treatment of children with ADHD in future clinical routine practice.